Analisis Literasi Masyarakat Tentang Pengelolaan Keuangan Pribadi Terhadap Tabungan, Investasi, dan Pengeluaran - Vivi Armadhani; Hwihanus Hwihanus (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research aims to measure people's understanding of personal financial concepts, such as savings, investment and spending. Factors such as education, experience, and social and economic factors will be identified as influencing people's financial literacy levels. It is hoped that concrete recommendations will help in increasing financial literacy for the people of Nginden Jagkungan subdistrict, Surabaya. This research uses a quantitative descriptive approach. The type and source of research data is an important element in the research process. The data used in this research is primary data. The data analysis method used in this research uses the PLS (Partial Least Square) analysis application through the Smart PLS program. Financial literacy with the Insurance, Investment and Financial Planning indicators has a positive effect of 0.540 and a significant 0.000% on Investment with the Knowledge of Investment and Market indicators. capital, financial literacy with indicators of Insurance, Investment and Financial Planning have a positive effect of 0.256 and a significant of 0.033% on Savings with indicators of Knowledge Interest and Confidence, Financial literacy with indicators of Insurance, Investment and Financial Planning have a positive effect of 0.632 and a significant of 0.000% on Expenditures with Knowledge indicators Availability of goods and services and price levels1. Financial literacy with insurance, investment and financial planning has a positive and significant effect on public investment with knowledge about investment and capital markets. 2. Financial literacy with insurance, investment and financial planning has a positive and significant effect on people's savings with financial knowledge. 3. Financial literacy with insurance, investment and financial planning indicators has a positive and significant effect on the level of public expenditure with knowledge of the availability of goods and services and price levels.